Sistema contable y toma de decisiones en la empresa Inversiones Díaz E.I.R.L. periodo 2021 - Valqui Linares, Paola Vanesa (2022)
The general objective of this research was to determine the degree of relationship between the accounting system and decision-making in the company Inversiones Díaz E.I.R.L. period 2021, taking the type of applied study and descriptive level - correlational and non-experimental design, where a population made up of 45 workers from the 4 company headquarters was included, who were surveyed through the survey technique and as instrument the questionnaire. Then, the research concludes that there is a considerable relationship between the operational characteristic and decision making, since it obtained a correlation coefficient of 0.847. Likewise, there is a considerable relationship between the ability to withstand changes and decision making, since there is a correlation coefficient of 0.770. On the other hand, to conclude that there is a considerable relationship between adaptability to new environments and decision making, since a correlation coefficient of 0.708 was obtained. Finally, it was possible to establish the relationship between the variables, that is, there is a considerable relationship between the accounting system and decision making, as confirmed by the correlation coefficient of 0.873, which, when considered positive and significant at the 0.01 level, rejects the null hypothesis, accepting the research hypothesis.